1997
DOI: 10.1111/j.1365-2133.1997.tb14902.x
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized study comparing itraconazole pulse therapy with continuous dosing for the treatment of toe–nail onychomycosis

Abstract: In this multicentre, double-blind, parallel group study, we evaluated the efficacy and safety of continuous treatment with itraconazole, 200 mg daily for 3 months, in comparison with itraconazole pulse therapy, 400 mg daily 1 week per month for 3 months, in the treatment of toe-nail onychomycosis. The study included 129 patients with distal subungual onychomycosis of the toe-nails, confirmed by microscopy and positive for dermatophyte culture; 65 received continuous treatment and 64 received pulse therapy. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Havu et al 21 found that the cure rate was not significantly different between 3 months of continuous treatment with itraconazole (200 mg/d) and an intermittent (1 week of treatment in every 4 [1:4]) regimen of 400 mg/d (N=121). De Doncker et al 20 evaluated 2 different intermittent schedules of itraconazole of 3 and 4 months (400 mg/d; 1:4 weeks) and found that the cure rates at 24 weeks were 64% for patients who received the shorter treatment and 72% for those who received 4 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Havu et al 21 found that the cure rate was not significantly different between 3 months of continuous treatment with itraconazole (200 mg/d) and an intermittent (1 week of treatment in every 4 [1:4]) regimen of 400 mg/d (N=121). De Doncker et al 20 evaluated 2 different intermittent schedules of itraconazole of 3 and 4 months (400 mg/d; 1:4 weeks) and found that the cure rates at 24 weeks were 64% for patients who received the shorter treatment and 72% for those who received 4 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…De Donker et al, 20 1996 Infected nail length (percentages), onycholysis, and subungual hyperkeratosis Incomplete Havu et al, 21 1997…”
Section: Incompletementioning
confidence: 99%
“…1). [11] However, the worldwide prevalence of onychomycosis is increasing. In one study that evaluated the prevalence and risk factors of onychomycosis in individuals representing different strata of population in New Delhi the prevalence of onychomycosis was conÞ rmed in 45% of the analysed patients.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Pulse therapy with itraconazole embodies dosing for 1 week (pulse) per month for a set number of months [17]. The instances of regimens that have been investigated for safety and efficacy in randomized trials included a three and a four pulse regimen with doses of 200 mg of itraconazole twice daily [18,19] and a two pulse regimen with 200 mg of itraconazole twice daily [17,[20][21][22]. Data from clinical practice and clinical trials indicate that the 1-week pulse regimen of itraconazole is well tolerated and associated with a favorable safety profile [23].…”
Section: Second Generation Oral Antifungalsmentioning
confidence: 99%